Deflected Pathways: Becoming Aggressive, Socially Withdrawn, or Prosocial With Peers During the Transition to Adolescence. (8th January 2015) - Monahan, Kathryn C.; Booth‐LaForce, Cathryn
Abstract : Although research has suggested strong continuity in children's adaptive or maladaptive behavior with peers across the transition to adolescence, less is known about deflected developmental pathways of peer social competence across this transition. This study investigates how mother–child and best friend relationship quality predict the deflection of youth from adaptive to maladaptive behavior with peers or the reverse. Using data from the NICHD Study of Early Child Care and Youth Development ( N = 1, 055), high‐quality friendships were associated with changes in peer social competence from 3rd to 6th grade. More positive and fewer negative interactions with a friend were linked with becoming more prosocial with peers, whereas less positive interactions with a friend were linked to becoming aggressive or withdrawn.